Familial reactive perforating collagenosis. - Tambe Swagata, A.; Ghate Smita, S.; Dhurat Rachita, S. (European Journal of Pediatric Dermatology, 2011)
Reactive perforating collagenosis (RPC) is a rare disorder characterized by transepidermal elimination of genetically altered collagen. Depending upon age of presentation it is classified into the 2 distinct forms. An inherited form usually manifests in childhood while an acquired, sporadic form occurs in adulthood, the latter being more frequent than the inherited form. We report a case of inherited type of RPC in a daughter and her mother.